LncRNA MALAT1 Aggravates Renal Tubular Injury via Activating LIN28A and the Nox4/AMPK/mTOR Signaling Axis in Diabetic Nephropathy - Song, Panai; Chen, Yinyin; Liu, Zhiwen; Liu, Hong; Xiao, Li; Sun, Lin; Wei, Jiali; He, Liyu (Frontiers in Endocrinology, 2022)
Background: Diabetic nephropathy (DN) is a serious complication among patients with diabetes. Elucidating its pathogenesis is crucial for identifying novel biomarkers and therapeutic targets for DN. Methods: DN tissues were harvested for examining MALAT1, LIN28A and Nox4. Human kidney-2 (HK-2) cells were treated with high glucose (HG) for establishing a cell model of DN. Cell viability was examined by MTT assay. HG-induced cell apoptosis and secretion of TNF-α and IL-6 were analyzed by TUNEL and ELISA assays, respectively. RIP and RNA pull-down assays were applied to analyze the interaction between MALAT1, LIN28A and Nox4 in HK-2 and human embryonic kidney 293T (HEK-293T) cells. A rat model of DN was established to determine the role of MALAT1 in DN in vivo. Results: MALAT1, LIN28A and Nox4 were upregulated in DN tissues and HG-treated HK-2 cells. Overexpression of MALAT1, LIN28A or Nox4 reduced cell viability and enhanced cell apoptosis, ROS generation and secretion of inflammatory cytokines in HG-treated HK-2 cells, whereas knockdown of MALAT1, LIN28A or Nox4 exerted opposite effects. Furthermore, MALAT1 directly interacted with LIN28A. Moreover, MALAT1 facilitated the interaction between LIN28A and Nox4 to increase Nox4 stability. Knockdown of Nox4 relieved HG-induced injury by suppressing the AMPK/mTOR signaling in HK-2 cells. Knockdown of MALAT1 alleviated renal tubular epithelial injury by suppressing LIN28A and the Nox4/AMPK/TOR signaling in DN. Conclusion: MALAT1 activates the AMPK/mTOR signaling via interacting with LIN28A to stabilize Nox4 mRNA, thereby aggravating high glucose-induced renal tubular epithelial injury. Our findings provide potential therapeutic targets for DN.